From child social impairment to parenting stress in mothers of children with ASD: The role of parental self-efficacy and social support - Li, Fēi; Xu, Mingyu; Wu, Danping; Tang, Yun; Zhang, Lingli; Liu, Xin; Zhou, Li; Li, Fei; Jiang, Liping (Frontiers in Psychiatry, 2022)
Objectives: Children with autism spectrum disorder (ASD) can exhibit persistent deficits in social communication, causing their mothers to experience elevated parenting stress during the childrearing process. Some internal and external psychosocial resources may mediate or moderate the mother-child relationship, though the underlying mechanisms remain unclear. This study aimed to explore the predictors of parenting stress in mothers of children with ASD and elucidate the mechanisms underlying the relationship between child social impairment and parenting stress. Methods: A cross-sectional study was conducted between October 2020 and March 2022 in Shanghai, China. Mothers of children with ASD completed a survey investigating child social impairment, parenting stress, parental self-efficacy, and social support. Results: A total of 185 mothers of children with ASD were included in the final analysis. 70.27 percent of mothers experienced a clinically significant level of parenting stress. Child social impairment (r = 0.46, P < 0.001), parental self-efficacy (r = -0.58, P < 0.001), and social support (r = -0.35, P < 0.001) were significantly correlated with parenting stress. Parental self-efficacy completely mediated the relationship between child social impairment and parenting stress (B = 0.51, P < 0.001), after controlling for socioeconomic status (SES) correlated with parenting stress. There was no significant moderating effect of social support between child social impairment and parenting stress (B = 0.01, P = 0.09). Conclusion: Future early intervention programs that focused on child’s social communication skills and empowered mothers with related strategies through group-based parent training programs may help reduce parenting stress.